Outcome of Total Knee Replacement in Morbid Obese Patients - Haziq Dad Khan, Sayed Sohail Akhtar, Waleed Ali, Adil Saidullah, Summar Fatima (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of our study was to determine the outcomes of total knee replacement in morbidly obese patients. Methodology: This prospective analysis was carried out on 128 morbidly obese patients (BMI> 40 kg/m2) in the Department of Orthopedic Surgery, Federal Govt. Polyclinic Hospital (FGPC) Islamabad, Mardan Medical Complex, Mardan and Bacha Khan Medical Complex, Swabi for the duration from January, 2021 to June, 2022. Demographic details, anthropometric parameters, and radiological assessment were recorded. Pre and post-operative radiological assessments included alignment, implant position, and radiolucent lines presence around the implant were compared. Outcome of TKR such as pre and post-operative functional score, knee society score, age, diagnosis, gender, laterality, and type of prosthesis were assessed and compared. SPSS version 25 was used for data analysis. Results: Of the total 128 TKR in morbid obese patients, the incidence of unilateral and bilateral TKR was 10 (7.8%) and 118 (92.2%) respectively. The overall mean age of the patients was 62.00 ± 8.12 years. Out of 126 TKR patients, there were 11 (8.6%) males and 117 (91.4%) females. Out of 10 unilateral TKR groups, males and females were 4 (40%) and 6 (60%) respectively. In the bilateral TKR group, there were 7 (5.9%) males and 111 (94.1%) were females. The mean BMI was 42.84 ± 3.46 kg/m2 with a range of 40-60 kg/m2. Based on Knee Society Scores and Functional Scores, Pre-operative mean knee score and functional score was 26.4 and 48.8, p=0.01 compared to post-operative 83.7 and 74.2, p=0.07 respectively. A higher prevalence for post-operative radiolucent lines was 28% against pre-operative 9%, p=0.01 were observed. During follow-up, the complications rate was 17.2% (n=22). Post-TKR complications such as superficial wound infection, deep joint infection, and deep vein thrombosis was found in 12.5% (n=16), 1.6% (n=2), and 3.1% (n=4) respectively. Conclusion: Our study found that prior to total knee replacement, patients with BMI>40 kg/m2 should lose weight to maintain weight reduction criteria. Knee arthroplasty’s growth rate and epidemiological changes in morbid obese patients were the particular issues regarding total knee replacement highlighted in the present study. Based on our study, morbidly obese patients could be suitable candidates for total knee replacement. Morbid obese patients should be counseled. Keywords: Total Knee Replacement, Unilateral, Bilateral, Morbid Obese Patients